Multiple ferroic glasses via ordering. (December 2015) - Monroe, J.A.; Raymond, J.E.; Xu, X.; Nagasako, M.; Kainuma, R.; Chumlyakov, Y.I.; Arroyave, R.; Karaman, I.
Graphical abstract: Simple heat treatments in the Ni45 Co5 Mn36.6 In13.4 magnetic shape memory alloy leads to the observation of multiple first and second order phase transitions including strain and magnetic glassy states through change in the degree of configurational order. Phase diagram above shows the influence of heat treatments on the Curie ( T C ), martensite start ( T Ms ), spin glass freezing ( T f ), supercooled austenite ( T ∗ ), strain glass freezing ( T g ) and Kauzmann ( T K ) temperatures. Abstract: Structural glasses are characterized by the loss of long-range translational and rotational symmetry. In the last two decades, however, it has been discovered that materials that exhibit ferroic (ferromagnetic, ferroelectric and ferroelastic) phase transformations may also exhibit glassy behavior, in which the ferroic degrees of freedom (magnetization, polarization, strain) exhibit a loss of long-range translational symmetry. A consequence of this loss of long-range symmetry is the suppression of the ferroic phase transitions. Moreover, these unique glassy systems exhibit dynamic and thermodynamic behavior analogous to regular structural glasses. Conventionally, the onset of glassy behavior is brought about by the introduction of spatial heterogeneities, typically originating from point defects, particularly in the case of strain glasses. Here, we demonstrate, for the first time, that configurational order/disorder in a single ferromagnetic alloy (Ni45 Co5 Mn36.6 In13.4 ) can be used to stabilize both strain and magnetic glasses. The control of the degree of configurational order – through simple heat treatment schedules –, and simultaneous application of stress and magnetic field enabled us to observe a Kauzmann point, that is, the collapse of the entropy difference between a crystalline and a glassy phase. Systematic investigation of the transformation behavior in this system as a function of heat treatment enabled us to observe four kinds of solid–solid phase transitions (ferromagnetic–paramagnetic, martensitic transformation, strain and magnetic glass) in a single composition. The alloy investigated can be used to further elucidate the nature of ferroic glass transitions and their coupling.